(untitled) (Advancements in Homeopathic Research, 2024)
Introduction: ADHD is the most common neurobe havioral disorder in children which comprises of 3 types: inattentive/hyperactive-impulsive/combined type. There are varied drugs in homoeopathy belong ing to narcotic groups which seems to be effective in these type of cases. These groups have various alka loids whose main sphere of action is on CNS or PNS as stimulant, depressor or hypnotic. Case summary: Here, 3 cases are presented with different types of ADHD as diagnosed by Vanderbilt Diagnostic Scale. In all these cases homoeopathic drug remedies were prescribed on the basis of totality of symptoms. Marked improvement in all the cases substantiate the effectiveness of homoeopathy especially drug remedies in these type of behavioural problems when given constitutionally.